2019
DOI: 10.1016/j.ejor.2018.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Scenario analysis to support decision making in addressing wicked problems: Pitfalls and potential

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 98 publications
1
24
0
6
Order By: Relevance
“…Ladner pointed out the quantitative analysis was inadequate to make that decision and that a qualitative ethnography study was required. As with our discussion, they were not arguing that qualitative methods should replace quantitative methods but should be used in a complementary manner (Evans, 2016;Wright et al, 2018). Soft OR methods help give understanding to the problem before any quantitative analysis has been conducted.…”
Section: Generality Of the Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Ladner pointed out the quantitative analysis was inadequate to make that decision and that a qualitative ethnography study was required. As with our discussion, they were not arguing that qualitative methods should replace quantitative methods but should be used in a complementary manner (Evans, 2016;Wright et al, 2018). Soft OR methods help give understanding to the problem before any quantitative analysis has been conducted.…”
Section: Generality Of the Resultsmentioning
confidence: 93%
“…Other case studies purely focus on showing soft OR benefit and are of limit educational value (Checkland and Scholes, 1999;Eden and Ackermann, 2001;Rosenhead and Mingers, 2001;Ritchey, 2006;Mingers, 2009). An overview of other examples of showcasing case studies can be found in Wright et al (2018). These case studies tend to be written in a verbose scientific style which is difficult to follow for a non-academic (Collins and Hester, 2016).…”
Section: Valuementioning
confidence: 99%
“…As such, it provides a means to consider the pathdependence that results in multiple failed interventions in the same place, and whether a newly-conceived intervention is truly on a scale, or of a kind, to shift the locality onto an alternative path of development when many similar attempts have failed. Wright et al (2019) review other augmentations to the IL scenario approach and their ability to assist with socalled 'wicked problems', which bear some of the hallmarks of ontological uncertainty. A wicked problem is one that is 'ill-formulated, where the information is confusing, where there are many clients and decision makers with conflicting values, and where the ramifications in the whole system are thoroughly confusing' (Churchman, 1967, p. B-141).…”
Section: Insert Table 1 Herementioning
confidence: 99%
“…A central requirement for tackling wicked problems is holism, implying the inadequacy of standard statistical-modelling approaches such as regression analysis, which tackle problems by breaking them into component parts, and examining the effect of each in isolation (Byrne, 2002). In reviewing scenario tools that can assist better with wicked problems, Wright et al (2019) highlight the Critical Scenario Method (CSM) (Cairns et al, 2010;Cairns et al, 2016).…”
Section: Insert Table 1 Herementioning
confidence: 99%
See 1 more Smart Citation